PENINGKATAN KEMAMPUAN GURU SDN NGARGOGONDO MAGELANG DALAM MELAKUKAN PENILAIAN MELALUI WORKSHOP EVALUASI KURIKULUM 2013 - Aslam Aslam; Sri Lestari Handayani; Zulherman Zulherman (JMM (Jurnal Masyarakat Mandiri), 2021)
Abstrak: Kegiatan pengabdian ini telah dilakasnakan pada 25-26 Februari 2019 dan bermitra dengan SDN Ngargogondo Magelang Jawa Tengah. Tujuan kegiatan ini untuk meningkatkan pengetahuan dan memperdalam pemahaman guru dalam melakukan evaluasi pembelajaran khususnya penilaian yang digunakan pada kurikulum 2013. Peserta kegiatan pengabdian ini adalah 21 guru-guru perwakilan SDN di sekitar daerah Ngargogondo. Terdapat 4 sekolah yang menjadi peserta kegiatan pengabdian ini yaitu SDN Tanjungsari, SDN Ngargogondo, SDN Borobudur, dan SDN Wanurejo. Kegiatan pengabdin ini dilakukan berdasarkan informasi bahwa mayoritas guru di SD tersebut mengalami kesulitan dalam melakukan penilaian Kurikulum 13 yang berbasis komputer. Hal ini dikarenakan mayoritas guru belum mahir dalam mengoperasikan komputer dengan baik dan kemampuan guru dalam melakukan evaluasi masih minim sehingga dibutuhkan pelatihan yang cocok untuk mengatasi hal tersebut yaitu pelatihan penilaiakan K13. Langkah-langkah kegiatan yang akan dilakukan adalah (1) Tahap persiapan berupa observasi, pemantapan dan penentuan lokasi sasaran, dan komunikasi dengan mitra; (2) Tahap pelaksanaan berupa paparan materi dan simulasi; dan (3) Tahap evaluasi diberikan dengan diskusi hasil pelaksanaan kegiatan. Hasil. akhir kegiatan menunjukan bahwaMelalui pelatihan yang dilakukan, kompetensi guru-guru meningkat dalam melakukan evaluasi kurikulum 2013.guru-guru di SDN Ngargogondo dapat meningkatkan pengetahuan dan memperdalam pemahaman guru dalam melakukan evaluasi pembelajaran khususnya penilaian yang digunakan pada kurikulum 2013. Abstract: This service activity has been carried out in partnership with SDN Ngargogondo Magelang, Central Java. The purpose of this activity is to increase knowledge and deepen teachers' understanding in evaluating learning, especially the assessment used in the 2013 curriculum. The participants of this service activity are 21 teachers from SDN representatives around the Ngargogondo area. There are 4 schools participating in this service activity, namely SDN Tanjungsari, SDN Ngargogondo, SDN Borobudur, and SDN Wanurejo. This service activity was carried out based on information that the majority of teachers in the elementary school had difficulties in conducting computer-based Curriculum of 13 assessments. The steps of the activities to be carried out are (1) the preparation stage in the form of observation, stabilization and determination of target locations, and communication with partners; (2) The implementation stage is in the form of material exposure and simulation; and (3) the evaluation stage is given a question in the form of a post-test. The final result of the activity shows that the competence of teachers increases in evaluating the 2013 curriculum.This service activity was carried out on February 25-26, 2019, in partnership with SDN Ngargogondo Magelang, Central Java. The participants of this service activity were 21 teachers representing SDN around the Ngargogondo area. Four schools participate in this service activity, namely SDN Tanjungsari, SDN Ngargogondo, SDN Borobudur, and SDN Wanurejo. This service activity was carried out based on information that most teachers in the elementary school had difficulties conducting computer-based K13 assessments. This was because most teachers were not proficient in operating computers properly, and the ability of teachers to conduct evaluations was still minimal, so that appropriate training is needed to overcome this, namely K13 assessment training. The steps of the activities to be carried out are: 1) The preparation stage in the form of observation, stabilization, and determination of target locations, and communication with partners; 2) The implementation stage is in the form of material exposure and simulation; and 3) Evaluation stage. Teachers at SDN Ngargogondo can increase knowledge and deepen teachers' understanding in evaluating learning, especially the assessment used in the 2013 curriculum.